Evaluation of thermal performance naturally ventilated classroom at tropical climate / Ernisuhani Mohamad Zamri, Asmat Ismail and Azizah Md Ajis - Mohamad Zamri, Ernisuhani; Ismail, Asmat; Md Ajis, Azizah (2019)
A naturally ventilated classroom has a significant impact on indoor thermal performance, especially in a tropical climate. This paper presents an evaluation of thermal comfort parameter in a naturally ventilated classroom located in Malaysia. For this study, a field experiment was conducted in Behrang, Perak to measure the indoor thermal comfort parameter. There were two case study classrooms selected for the experimentation with different orientations, which are Southeast for Classroom A and Northwest for Classroom B. The field experiment was conducted in November till December 2018. Air temperature, air velocity, relative humidity and mean radiant temperature were measured in this study to evaluate the classrooms’ indoor performance. At the same time, the outdoor air temperature, air velocity and relative humidity were measured concurrently. The data was collected for three days during sunny days as well as clear sky. A result of data analysis found that there is a positive relationship between outdoor and indoor temperature and outdoor and indoor relative humidity. As conclusion, this study found that an outdoor parameter influenced the indoor performance in a naturally ventilated classroom. Also, the orientation and external condition of the classroom has a significant influence on indoor thermal performance